Causal associations between gut microbiota and cutaneous melanoma: a Mendelian randomization study - Bao, Yan-Qiu; Zhang, Ying; Li, Zhou-Na (Frontiers in Microbiology, 2024)
Background: Cutaneous melanoma (CM) of the skin stands as the leading cause of mortality among skin cancer-related deaths. Despite the successes achieved with novel therapies such as immunotherapy and targeted therapy, their efficacy remains limited, necessitating further exploration of new treatment modalities. The gut microbiota and CM may be linked, as indicated by a growing body of preclinical and observational research. Nevertheless, the exact correlation between the intestinal microbiota and CM remains to be determined. Therefore, this study aims to assess the potential causal relationship between the gut microbiota and CM.The study utilized exposure data obtained from the MiBioGen consortium's Microbiome GWAS, which included a total of 18,340 samples gathered from 24 population-based cohorts. Data at the summary level for CM were acquired from the UK Biobank investigation. The main analytical strategy utilized in this research was the Inverse Variance Weighted (IVW) technique, supported by quality assurance measures like the Weighted Median Model, MR-Egger, Simple Model, and Weighted Model approaches. The Cochran's Q test was used to evaluate heterogeneity. To ascertain potential pleiotropy, we employed both the MR-Egger regression and the MR-PRESSO test. Sensitivity analysis was conducted using the leave-one-out method.The study found that the class Bacteroidia (OR=0.997, 95% CI: 0.995-0.999, p =0.027), genus Parabacteroides (OR=0.997, 95% CI:0.994-0.999, p =0.037), order Bacteroidales (OR=0.997, 95% CI:0.995-0.999, p =0.027), and genus Veillonella (OR=0.998, 95% CI:0.996-0.999, p =0.046) have protective effects on CM. On the order hand, the genus Blautia (OR=1.003, 95% CI:1-1.006, p =0.001) and phylum Cyanobacteria (OR=1.002, 95% CI:1-1.004, p =0.04) are identified as risk factors for CM.We comprehensively assessed the potential causal relationship between the gut microbiota and CM and identified associations between six gut microbiota and CM. Among these, four gut microbiota were identified as protective factors for CM, while two gut microbiota were identified as risk factors for CM. This study effectively established a causal relationship between the gut